Who participates and who doesn't? Adapting community participation model for developing countries - Swapan, Mohammad (ELSEVIER SCI LTD, 2016)
In developing countries, the idea of community participation has been advocated largely by development scholars and practitioners inspired by western-based models. Such prescriptions for community participation focus largely on institutional reforms while ignoring social, political and psychological factors that also affect individuals' propensity to participate in the planning processes. Theoretical models that explain citizens' participation in the planning processes found in the extant literature do not adequately reflect the widespread realities of developing countries. Moreover, prior studies suggest that only few citizens, irrespective of diverse socio-economic background, have interest in participating in the planning process. Traditional participation spectrum views participation from a citizen activist's perspective and is, perhaps, sceptical of participation choices generated within current political context. In this article, it is contended that the rational decision-making employed by citizens in determining whether or not to be involved in the planning process defines the spectrum of participation. Reporting on a case study of the megacity – Dhaka – this article seeks to develop a community participation model that represents participants' realities as well as their aspiration to engage in decision-making and reflects the reasons for public apathy on participation. The empirical study identifies a range of social, political and psychological factors affecting an individual's attitude towards participation. These include an individual's lack of awareness, involvement in informal networks, discouraging perceptions about participation outcomes and most notably, lack of trust in the planning system. Citizens tend to avoid engaging in formal participation processes as the prevalent parallel system based on informal transactions with political leaders is perceived to be more effective than the formal planning system.